Permainan Simulus gerak motorik pada anak kelas 6 SD Muhammadiyah Bligo 01, Buaran Pekalongan - nurbuwono, rohma howo; Fasy, Nurul Aqil Nahari; Saputra, Fikki Arifani; Putri, Mega Widya (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2024)
This activity aims to train the accuracy and concentration of grade 6 students at SD Muhammadiyah Bligo 01 Buaran Wiradesa. Exercise is vital to a child's health and physical development, and effective testing can help identify areas that need improvement. This activity takes 6th grade students as test subjects. The motor tests used focus on various aspects, such as locomotor, non-locomotor and manipulative movements. The results of the activity show that the motor test used at SD Muhammadiyah Bligo 01 Buaran, Pekalongan has several advantages but also has disadvantages. The advantages include ease of implementation, while the weaknesses include the lack of factors that consider aspects of student health as a whole. Based on the results of the activity, recommendations for improvements are proposed to increase the accuracy and suitability of the test. This activity provides valuable information regarding the motor tests used at SD Muhammadiyah Bligo 01 Buaran, Pekalongan.